DAILY JOURNAL OF GRATITUDE AS THE IMPLEMENTATION OF POSITIVE PSYCHOLOGY IN STUDENT PERSONALITY DEVELOPMENT GUIDANCE AND COUNSELING PROGRAM - Yudhawati, Dian (Jurnal Internasional Bisnis, Humaniora, Pendidikan dan Ilmu Sosial, 2019)
Abstract—The theory of positive psychology pioneered by Martin Seligman focuses on efforts to explore and developcharacters as the human strengths. By exploring and developing the positive side of the individual will lead someone tohave true happiness. Human life will be meaningful if the positive side of humans can be maximally developed. Byapplying positive psychology, it is expected that lecturers can carry out guidance and counseling for the development ofstudent personalities. Personality developments needed are intrapersonal, interpersonal, problem solving, learning andprofessional skills. The Daily Journal of Gratitude is an activity that can be applied to motivate the growth of gratefulhabit which is an aspect of positive psychology. Gratitude as a cognitive construction is shown by acknowledging mercyand kindness for the blessings that have been received by a person and focusing on the positive things. The connectionwith personality development is the ability of students to develop intrapersonal skills. As an emotional construction,gratitude is characterized by the ability to change the emotional response to a thing happened so that it becomes moremeaningful. This is related to the development of students when facing other people or the ability to developinterpersonal skills. Gratitude emotions involve feelings of amazement, gratitude, appreciation and happiness for theblessings and the life to be lived. Gratitude as a construction of behavior is kind of respond in return to others for thebenefits and gifts received . Personality development in the construction of behavior is related to learning skills,problem solving skills and professional skills. By applying the Daily Journal of Gratitude it is hoped that students canbe guided and counseled to become individuals who are able to develop optimally in their lives on campus up to thegraduation day, so that they can have the skills to interact in a complex and diverse multigeneration environment.